Design, Synthesis and Magnetism of Single-molecule Magnets with Large Anisotropic Barriers - Lin, Po-Heng (Université d'Ottawa / University of Ottawa, 2012)
This thesis will present the synthesis, characterization and magnetic measurements of lanthanide complexes with varying nuclearities (Ln, Ln2, Ln3 and Ln4). EuIII, GdIII, TbIII, DyIII, HoIII and YbIII have been selected as the metal centers. Eight polydentate Schiff-base ligands have been synthesized with N- and mostly O-based coordination environments which chelate 7-, 8- or 9-coordinate lanthanide ions. The molecular structures were characterized by single crystal X-ray crystallography and the magnetic properties were measured using a SQUID magnetometer. Each chapter consists of crystal structures and magnetic measurements for complexes with the same nuclearity. There are eight DyIII SMMs in this thesis which are discrete molecules that act as magnets below a certain temperature called their blocking temperature. This phenomenon results from an appreciable spin ground state (S) as well as negative uni-axial anisotropy (D), both present in lanthanide ions owing to their f electron shell, generating an effective energy barrier for the reversal of the magnetization (Ueff). The ab initio calculations are also included for the SMMs with high anisotropic energy barriers to understand the mechanisms of slow magnetic relaxation in these systems.
Keywords: Single-Molecule Magnets; Anisotropic Barrier; Lanthanide